PENGARUH NILAI TUKAR, TINGKAT BUNGA, INFLASI, DAN JUMLAH UANG BEREDAR TERHADAP INDEKS HARGA SAHAM SEKTOR KEUANGAN DI BURSA EFEK INDONESIA (BEI) (Studi Kasus pada Indek Harga Saham Sektor Keuangan Di BEI) - Amna Mawardi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
In the midst of uncertain economic condition, nowadays people tend to secure the potential assests they have, and think how to take advantage of the assets they have in order to keep it high in value for a long period of time. One of the way is by invest in the form of securities traded in the capital market. That is why every investor in the capital market urgently require a relevant informations on trend of transactions as reference in making investment decisions. One of the required information is stock market index. The purpose of this study is to examine the effect 0f macro economic indicators, US Dollar exchange rate, interest rate, inflation rate, and money supply on stock market index in Indonesia Stock Exchange (IDX). The method used in this research is using multiple linear regression. Data obtained from SEKI - Bank Indonesia (Economic and Financial Statistics - Central Bank of The Republic of Indonesia) and IDX (Indonesia Stock Exchange), in the form of secondary data of monthly period in year 2011 – 2015, collected by documentation techniniques. The results showed that partially variable of US Dollar exchange rates, interest rates, inflation rates, and money supply have no effect on the stock price index of financial sector. Whereas universally interest rates have a significant positive effect on the stock price index of financial sector. Over all simultaneously US Dollar exchange rates, interest rates, inflation rates, and money supply have an effect on the stock price index of financial sector. Keywords: exchange rate, interest rate, inflation rate, money supply, and stock market index.